Changes in Bank Service Quality After Merger: A Case Study on Banks in Indonesia - Alexander, Gloria; Tetimau, Felicia Edlyn; Mahendra, Adrian; Linawati, Nanik (PT Mattawang Mediatama Solution, 2025)
Bank mergers are a strategic initiative aimed at enhancing financial stability, expanding market share, and improving service efficiency. This study examines the impact of bank mergers on service quality in Indonesia, with a particular focus on customer satisfaction, operational efficiency, and brand trust across three different generations (gen X, millennials, & gen Z). Using qualitative methods, this research analyzes survey data derived from news articles and customer feedback from banks that underwent mergers between 2018 and 2023. The findings indicate that bank mergers often result in improved digital services, broader service offerings, and greater operational efficiency. However, they may also lead to short-term challenges, including service disruptions, policy changes, and shifts in brand identity. These disruptions can create uncertainty around product offerings, pricing, and service consistency, potentially affecting overall customer satisfaction. Nevertheless, banks that effectively manage post-merger integration—through transparent communication, consistent service delivery, and proactive customer engagement—are better positioned to retain customer loyalty. Moreover, brand reputation and perceived stability play a crucial role in shaping customer trust and retention following a merger. While mergers offer significant opportunities for growth and innovation, they also pose risks to customer relationships if not carefully managed. Therefore, understanding these dynamics is essential for banks seeking to address customer concerns, strengthen retention strategies, and realize the long-term benefits of mergers.